Economics of the Public Sector - "Stiglitz, Joseph E." (W.W. Norton)
What should be the role of government in society? How should it design its programmes? How should tax systems be designed to promote both efficiency and fairness? Nobel Laureate Joseph Stiglitz and new co-author Jay Rosengard bring an unparalleled level of expertise to address these key issues of public-sector economics. No other text is as modern, as accessible, or incorporates as much first-hand policy-advising experience by its authors as Stiglitz/Rosengard.
Keywords: Finance